Standardized Treatment and Assessment Pathway Improves Mortality in Adults With Methicillin-resistant Staphylococcus aureus Bacteremia: STAPH Study. (23rd May 2021) - Alosaimy, Sara; Lagnf, Abdalhamid M; Morrisette, Taylor; Jorgensen, Sarah C J; Trinh, Trang D; Zasowski, Evan J; Scipione, Marco R; Zhao, Jing J; Mynatt, Ryan; Herbin, Shelbye; Dhar, Sorabh; Chopra, Teena; et al.
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI) management remains challenging for clinicians. Numerous in vitro studies report synergy when vancomycin (VAN) and daptomycin (DAP) are combined with beta-lactams (BLs), which has led to clinical implementation of these combinations. While shorter durations of bacteremia have often been reported, there has been no significant impact on mortality. Methods: The Detroit Medical Center (DMC) developed and implemented a clinical pathway algorithm for MRSA BSI treatment in 2016 that included the early use of BL combination therapy with standard of care (VAN or DAP) and a mandatory Infectious Diseases consultation. This was a retrospective, quasi-experimental study at the DMC between 2013 and 2020. Multivariable logistic regression was used to assess the independent association between pathway implementation and 30-day mortality while adjusting for confounding variables. Results: Overall, 813 adult patients treated for MRSA BSI were evaluated. Compared with prepathway (PRE) patients (n = 379), those treated postpathway (POST; n = 434) had a significant reduction in 30-day and 90-day mortality: 9.7% in POST vs 15.6% in PRE ( P = .011) and 12.2% in POST vs 19.0% in PRE ( P = .007), respectively. The incidence of acute kidney injury (AKI) was higher in the PRE compared with the POST group: 9.6% vs 7.2% ( P = .282), respectively. After adjusting for confounding variables including Infectious Diseases consult, POST was independently associated with a reduction in 30-day mortality (adjusted odds ratio [aOR], 0.608; 95% CI, 0.375–0.986). Conclusions: Implementation of an MRSA BSI treatment pathway with early use of BL reduced mortality with no increased rate of AKI. Further prospective evaluation of this pathway approach is warranted.